2022
DOI: 10.3390/molecules27186032
|View full text |Cite
|
Sign up to set email alerts
|

Seaweeds in the Oncology Arena: Anti-Cancer Potential of Fucoidan as a Drug—A Review

Abstract: Marine natural products are a discerning arena to search for the future generation of medications to treat a spectrum of ailments. Meanwhile, cancer is becoming more ubiquitous over the world, and the likelihood of dying from it is rising. Surgery, radiation, and chemotherapy are the mainstays of cancer treatment worldwide, but their extensive side effects limit their curative effect. The quest for low-toxicity marine drugs to prevent and treat cancer is one of the current research priorities of researchers. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 192 publications
0
21
0
Order By: Relevance
“…Fucoidans have been shown to exhibit a variety of beneficial pharmacological effects, including antitumor [ 5 , 54 , 55 , 56 , 57 , 58 ], anti-inflammatory [ 3 , 4 , 5 ], immunomodulatory [ 4 , 5 ] antioxidant [ 6 , 7 , 8 ], anticoagulant [ 5 , 59 , 60 , 61 , 62 ], antithrombotic [ 5 , 63 , 64 ], antiangiogenic [ 5 , 56 , 65 , 66 , 67 , 68 , 69 ], and antiviral [ 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Overview Of Fucoidansmentioning
confidence: 99%
See 1 more Smart Citation
“…Fucoidans have been shown to exhibit a variety of beneficial pharmacological effects, including antitumor [ 5 , 54 , 55 , 56 , 57 , 58 ], anti-inflammatory [ 3 , 4 , 5 ], immunomodulatory [ 4 , 5 ] antioxidant [ 6 , 7 , 8 ], anticoagulant [ 5 , 59 , 60 , 61 , 62 ], antithrombotic [ 5 , 63 , 64 ], antiangiogenic [ 5 , 56 , 65 , 66 , 67 , 68 , 69 ], and antiviral [ 70 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Overview Of Fucoidansmentioning
confidence: 99%
“…The antitumor mechanisms of fucoidans in these tumor cells (e.g., A549, MCF-7) include cell cycle arrest at the sub- / phase [ 79 , 80 , 81 , 82 ], caspase-dependent apoptosis [ 80 , 81 , 83 ], regulation of specific apoptotic proteins (e.g., poly [ADP-ribose] polymerase 1 (PARP1) [ 84 , 85 , 86 ], protein kinase RNA-like endoplasmic reticulum kinase (PERK), B-cell lymphoma 2 (Bcl-2) [ 84 ], BAX [ 84 , 87 ], and caspases -3, -8, and -9 [ 80 , 84 , 86 ]). Increasing evidence has shown that fucoidans are capable of exhibiting direct and indirect inhibitory effects on tumor cells by regulating several important signaling pathways, such as extracellular signal-regulated kinase 1/2 (ERK1/2) [ 56 , 84 , 88 ], phosphoinositide 3-kinase-Akt (PI3K/Akt) [ 84 , 88 ], p38 mitogen-activated protein kinase (p38 MAPK) [ 84 ], and mammalian target of rapamycin (mTOR) pathways [ 87 , 88 ].…”
Section: Overview Of Fucoidansmentioning
confidence: 99%
“…Bisindole alkaloids, terpenes, sesquiterpenoid lactone, and diterpenoids from green seaweeds have promising antitumor activity by suppressing tumor-inducing molecular markers (Pradhan et al, 2020;Tanna et al, 2020). Fucoidan arrests the cell growth cycle and enhances apoptosis by inhibiting VEGF (vascular endothelial growth factor) and natural killer cell activation (Ganesan et al, 2019;Jin et al, 2022). Similarly, laminarin, dieckol, and phloroglucinol enhance the apoptosis signal pathways in colon cancer (Weinberg, 2013), pancreatic cancer (Xu et al, 2021), and breast cancer (Hoadley et al, 2018) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The diverse pharmacological actions of fucoidan are still under investigation but it has been reported to affect many pathophysiological processes, such angiogenesis, carcinogenesis, oxidative stress, immune modulation and inflammation (Kwak, 2014;Jin et al, 2022). Both in vitro and in vivo studies have consistently confirmed the anti-cancer potential of fucoidan via the inhibition of angiogenesis, induction of cell cycle arrest and apoptosis (Aisa et al, 2005;Zhang et al, 2011;Atashrazm et al, 2015) and down regulation of CDK4, cyclin D1 and cyclin D2 in cancer cells (Banafa et al, 2013;Boo et al, 2013) [reviewed in more details in (Atashrazm et al, 2015) and (Jin et al, 2022)].…”
Section: Introductionmentioning
confidence: 99%
“…The diverse pharmacological actions of fucoidan are still under investigation but it has been reported to affect many pathophysiological processes, such angiogenesis, carcinogenesis, oxidative stress, immune modulation and inflammation (Kwak, 2014;Jin et al, 2022). Both in vitro and in vivo studies have consistently confirmed the anti-cancer potential of fucoidan via the inhibition of angiogenesis, induction of cell cycle arrest and apoptosis (Aisa et al, 2005;Zhang et al, 2011;Atashrazm et al, 2015) and down regulation of CDK4, cyclin D1 and cyclin D2 in cancer cells (Banafa et al, 2013;Boo et al, 2013) [reviewed in more details in (Atashrazm et al, 2015) and (Jin et al, 2022)]. Fucoidan also modulated a number of oncogenic signaling pathways known to be upregulated in cancer and involved in promoting tumour progression, for instance, the extracellular signal-regulated kinase (ERK) pathway (or RAS/RAF/MAPK pathway) (Aisa et al, 2005), PI3K/AKT/mTOR pathway (Lee et al, 2012) as well as the GSK and Wnt pathways (Boo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%